Biologically Inspired Catheter for Endovascular Sensing and Navigation - Sutton, Erin E.; Fuerst, Bernhard; Ghotbi, Reza; Cowan, Noah J.; Navab, Nassir (Scientific Reports, 2020)
Minimally invasive treatment of vascular disease demands dynamic navigation through complex blood vessel pathways and accurate placement of an interventional device, which has resulted in increased reliance on fluoroscopic guidance and commensurate radiation exposure to the patient and staff. Here we introduce a guidance system inspired by electric fish that incorporates measurements from a newly designed electrogenic sensory catheter with preoperative imaging to provide continuous feedback to guide vascular procedures without additional contrast injection, radiation, image registration, or external tracking. Electrodes near the catheter tip simultaneously create a weak electric field and measure the impedance, which changes with the internal geometry of the vessel as the catheter advances through the vasculature. The impedance time series is then mapped to a preoperative vessel model to determine the relative position of the catheter within the vessel tree. We present navigation in a synthetic vessel tree based on our mapping technique. Experiments in a porcine model demonstrated the sensor’s ability to detect cross-sectional area variation in vivo. These initial results demonstrate the capability and potential of this novel bioimpedance-based navigation technology as a non-fluoroscopic technique to augment existing imaging methods.
CRIS-Team Scopus Importer:2023-03-08